Implementasi Metode Prototype Pada ASDP Merak Banten Berbasis Android - Madona Septiana; TM Zaini (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2022)
ASDP Merak Banten is part of PT. ASDP Indonesia Ferry (Persero) which is engaged in crossing services at the port of Merak-Banten. In the Merak-Bakauheni Port crossing service, operational data for each ship is different. Data from the operational results of crossing each ship is processed by the ASDP Merak by recording it on the sheet of the operational form of the ship and recapitulated using the Microsoft Excel application. Searching for operational data on ships is also quite difficult, because officers do so by opening each file until the desired data is found. To simplify recapitulation of operational data on ships, an Android-based system was made. The system built is integrated with the parts related to the operational data processing of the ship. This system is based on Android with a minimum operating system version of use is 5.0 (Lollipop). System development methods used are prototypes and data collection methods using interviews and literature study. The programming language used in building this system is Java with a programming editor using Android Studio. The type of database used in this system is MySQL.The system that is built also has a ship's departure schedule that can be seen by passengers if the passenger installs this application.Key Words: ASPD Merak, Ship Operation, Prototype, Android, MySQL.